RESEARCH OF INFLUENCE OF ETHNOPSYCHOLOGICAL CONCEPTS ON INTELLECTUAL DEVELOPMENT - Berdibayeva S.K.; Syrgakbayeva A.S.; Madiyarova A.S.; Amirbekov Sh.A.; Alimzhanova A.Sh.; Onalbekov Y.S.; Berdibayev S.K.; Кonrad Resсhke (Scientific Journal of Pedagogy and Economics, 2020)
Intellect and ethnic values are formulated as adaptation to the environment. Intellectual development and ethnic views of children are closely interconnected, and this conclusion is mathematically proven in our experimental section. Intellectual indicators, based on development of ethnocultural values, are the basis of our research. As a result of studying the interrelations of intellectual development and ethnic views in children, it was shown that there are differences in motivation of behavior and human actions based on ethnocultural features. The purpose of the research: study of the relationship between intellectual development and ethnic views and their impact on the personal development of children. Research hypothesis: Ethnopsychological ideas have a positive effect on intellectual development. During the study, it was revealed that ethnic views of subjects of different ethnic groups positively influences the development of both intellectual and personal development of children. In the psychological science of Kazakhstan for the first time it has been determined that the interrelation of intellectual development and ethnic views positively affects the development of personality. Ethnocultural values are very close to ethnic consciousness and can be the basis of intellectual development. At the present stage of modern ethnic revival, special attention is paid to ethnicity. It was revealed that at an early age, respect for its features, knowledge of other ethnocultural values of people are the basis for intellectual and personal development.